PERSPEKTIF HUKUM ISLAM TERHADAP SISTEM PAYLATER DI ERA MODERN - Rezkianisa Awaliya; Ai Elsa Amalia Agistiani; Hendri Hendriawan (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
The advancement of financial technology in Indonesia has introduced PayLater or Buy Now Pay Later (BNPL) services, which are increasingly popular among Muslim communities. Nevertheless, the implementation of this system continues to raise debates regarding its conformity with Islamic legal principles. This study aims to examine the PayLater system from the perspective of Islamic law, particularly concerning contracts (akad), usury (riba), uncertainty (gharar), and the objectives of Islamic law (maqashid syariah). The research applies a qualitative method using a descriptive-analytical library research approach. Primary sources consist of the Quran, hadith, classical fiqh literature, and DSN-MUI fatwas, while secondary sources include academic journals, contemporary Islamic economics books, and OJK regulations. The study finds that conventional PayLater practices contain elements of riba qardh due to predetermined additional charges imposed at the beginning of the contract. Furthermore, elements of gharar are identified because of insufficient transparency in fee structures, alongside late-payment penalties that are inconsistent with DSN-MUI Fatwa No. 17 of 2000. From the perspective of maqashid syariah, the negative impacts (mafsadah) are considered greater than the benefits (maslahah) generated by the current practice. Therefore, this study recommends restructuring PayLater contracts through murabahah or bai’ muajjal schemes and encourages DSN-MUI to formulate a specific fatwa regarding BNPL services.